PEMETAAN PENGGUNAAN BAHASA MELAYU BANGKA - Putra Pratama Saputra; M Afifulloh (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2020)
This study aims to map the use of the Bangka Malay language. This research uses qualitative. The source of the data was observations, interviews with language users, and questionnaires focused on four districts, namely Bangka Regency, South Bangka Regency, Central Bangka Regency, West Bangka Regency, and one Madya City, Pangkalpinang. The reduction data for dialectological studies contain differences in phonological and lexical levels selected from all data obtained, except data in the form of phrases and sentences, while reduction data for comparative historical linguistic studies are collected from 200 basic Swadesh vocabularies (for lexicostatistic analysis), in which describe the word kin. The results of this study are as follows: a. The Malay language of Bangka has the same variation between user regions, especially those used in the City of Pangkalpinang, Sungailiat, Toboali, Koba, and Mentok; b. Some vocabularies are different between regions but are not significant because they occur only at the phonemic level such as the use of the words 'akar (root)' and 'aker', 'dingin (cold)' and 'dingen', 'dengar (hear)' and ‘denger'; c. Significant differences occur only in some of the vocabulary used by the Bangka community such as the word 'burn' which translates to 'menam', 'tembung', and 'tunu'; d. Vocabulary differences are generally found in remote areas such as Sadai, Air Gegas, and Kelapa.